Визначення впливу відбору соку у дифузійних апаратах на прибутковість бурякоцукрового виробництва - Масліков, Михайло Олександрович; Масліков, Максим Михайлович; Петренко, Валентин Петрович; Бойко, Володимир Олександрович (My University, 2021)
У статті наведені результати визначення впливу відбору соку у дифузійних апаратах на прибутковість бурякоцукрового виробництва. Виконано аналіз чинників, що впливають на ефективність висолоджування бурякової стружки, втрати цукрози в жомі, перехід у сік нецукристих речовин, а також цукрози в білий цукор і мелясу. Розроблено модель процесу та програму розрахунку оптимального коефіцієнта відбору дифузійного соку. За критерій оптимізації прийнято очікувану зміну прибутку виробництва цукру. Ця модель дає змогу прогнозувати прибутковість виробництва цукру з буряка залежно від умов виробництва і кон’юнктури цін на товари, що впливають на доходи і видатки виробництва. Наведені приклади розрахунку оптимального коефіцієнта відбору дифузійного соку й очікуваної зміни прибутковості.

Increase in water supply for extraction with a corresponding increase in raw juice draft is the main method to reduce sugar losses in the pulp. But this method has negative effects: reducing of sucrose crystallization efficiency, increasing costs for juice purification, heating and concentrating. Total profitability from draft increasing may increase or decrease, so we can discuss the optimal draft value. In this article, mathematical model is developed to calculate the optimal draft value for minimization the total operating costs. This model calculates the sugar losses in the pulp with equation, obtained the updated data on mass transfer during sugar extraction from beet cossettes. Mass transfer in the extractor between beet chips and extractant is analyzed with using the mass conductivity coefficient in solid phase systems. The proposed model also takes into account the presence of pulp pressing and returning the required amount of pulp water to the extractor. Factors influencing the efficiency of sucrose extraction are analyzed: sugar loss in the pulp, transition of sucrose to white sugar and to molasses, as well as transition of non-sugars to raw juice. The main technical and economic indicators are determined, which are significantly affected by the changes in draft. Computer model, based in expected profit of beet sugar production, is developed to calculate the optimal draft value and the opti mal sugar losses in the pulp for certain conditions. This model allows to predict the profitability of beet sugar production depending on the conditions of the manufacturing processes and on the prices for goods that affect income and expenses. Examples of calcula tions of the optimal draft and the expected change in profitability are presented
Keywords: екстракція; масообмін; втрати цукру; коефіцієнт відбору; extraction; sugar losses; mass transfer; draft value; кафедра теплоенергетики та холодильної техніки